Novel Evidence for the Increasing Prevalence of Unique Names in China: A Reply to Ogihara - Bao, Han-Wu-Shuang; Cai, Huajian; Jing, Yiming; Wang, Jianxiong (Frontiers in Psychology, 2021)
In this study, we aimed to address three comments proposed by Ogihara (2020) on a recent study where we found that unique names in China have become increasingly popular from 1950 to 2009 (Cai et al., 2018). Using a large representative sample of Chinese names (N = 2.1 million), we replicated the increase in uniqueness of Chinese names from 1920 to 2005, especially since the 1970s, with multiple uniqueness indices based on name-character frequency and name-length deviation. In particular, Chinese characters that are rare in daily life or naming practice were more often used in given names, and the length of given names became more deviant from typical practice (i.e., more one-character and three-character given names and higher standard deviation of name length). Taken together, these findings not only reconfirmed the increasing prevalence of unique names but also demonstrated the validity of various indices in assessing name uniqueness in China.